Um caminho interdisciplinar para o estudo de tópicos da física térmica - Sales, João Pedro Almeida (2020)
This work aims teaching topics of Thermal Physics in an interdisciplinary and nontraditional way, from an investigative teaching perspective, through an educational product in the form of teacher and student support material. Therefore considered the effects of interdisciplinarity in the process of teaching and learning of Thermal Physics, the use of an Inquiry-Based Teaching Sequences-IBTS and the vision of official documents governing high school. The work was designed from a investigation perspective, with the student being a participant with the possibility to plan, act, observe and analyze the procedures adopted. For an analysis of the results of the implementation of the work, considered quantitative and qualitative aspects. The main result was the development of an educational product entitled “An Interdisciplinary Path for the Study of Thermal Physics Topics”, which serves as a pedagogical support for basic education, available on the Internet in free. The main objective, which has been achieved, is to contribute to the cognitive, critical, academic and citizen formation of the students.